Synopsis of Couepia (Chrysobalanaceae) in Costa Rica, with a description of two new species - Santamaría-Aguilar, Daniel A.; Lagomarsino, Laura P. (Phytotaxa, 2015)
We provide a synopsis to the Costa Rican species of Couepia (Chrysobalanaceae), including a description of two new species: C. hallwachsiae and C. janzenii.